Overview of Routine Blood Tests for Typhoid Fever Patients at Bendan Regional General Hospital, Pekalongan City - Mahfudloh, Devi Syakirotul; Wibowo, Subur (INDOGENIUS, 2025)
Background & Objective: Typhoid fever is an acute infectious disease that remains a health problem in Indonesia due to its high morbidity and mortality rates. This disease is caused by Salmonella typhi or Salmonella paratyphi and can be diagnosed through routine blood tests. This study aims to determine the routine blood profile of typhoid fever patients at Bendan Regional General Hospital in Pekalongan City. Method: This study used a descriptive design with a sample of 30 patients. Routine blood tests were performed using an automatic hematology analyzer. Results: The results showed that 18 samples (60%) had normal leukocyte counts, 6 samples (20%) had high leukocyte counts, and 6 samples (20%) had low leukocyte counts. For monocytes, 22 samples (73.34%) were within normal levels, 7 samples (23.33%) showed high levels, and 1 sample (3.33%) showed low levels. Conclusion: In general, routine blood tests showing white blood cell and monocyte counts in samples from typhoid fever patients at Bendan Regional General Hospital in Pekalongan City were within normal limits.